Analysing the Relationship between Knowledge, Education Level and Economic Status with Early Marriage in Married Couples in Sindangheula Village, Serang Regency - Pusporini, Lenny Stia; Putri, Elsya Novia Ramadhani; Sulupadang, Prishilla (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Early marriage is a social issue that affects various aspects of community life, including individual and family welfare. Knowledge, education level, and economic status have been identified as factors that may influence of early marriage in the region. The purpose of this study was to determine the relationship between knowledge, education level, and economic status with early marriage in married couples in Sindangheula Village, Serang Regency in 2023. This study used a correlational method with a cross-sectional approach. The sample was 79 respondents selected using a random generator system where all names within the population were included in the system and then randomly chosen according to a predetermined quantity. Findings indicated a minority (20.3%) reported early marriage, while a significant proportion exhibited poor knowledge (35.4%) and low education levels (41.8%). Moreover, a minority (29.1%) reported poor economic status. Statistical analysis revealed significant relationships between knowledge (pv = .025), education level (pv = .001), economic status (pv = .002), and early marriage. Multivariate analysis further confirmed these associations (R2 = .154, adjusted R2 = .120, F = 4.540, Pv < 0.05), with a positive β value (0.263). The research results also revealed a positive β value (0.263). It is recommended that village officials can provide information and health education to adolescents and parents about marriage as well as provide motivation and beneficial activities for the development of the Sindangheula Village, Serang Regency.